2007
DOI: 10.1109/titb.2007.891926
|View full text |Cite
|
Sign up to set email alerts
|

A Radio Frequency Identification Implanted in a Tooth can Communicate With the Outside World

Abstract: A radio frequency identification (RFID) transponder covering the 13.56 MHz band was adapted to minimize its volume so that it could be placed in the pulp chamber of an endodontically treated human tooth. The minimized transponder had a maximum communication distance of 30 mm. In an animal experiment, the transponder was fixed in the cavity of a mandibular canine of a dog. An RFID reader positioned close to the dog's face could communicate with the transponder in the dog's tooth. In certain cases, the system is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The application of this passive approach for intraoral sensing has been already proposed and successfully implemented [38,39], in cases where the sensors is located just in the mouth and outside the tooth. However, the use of RFID passive tags to be put inside the tooth has been proposed and experimentals on animals have been performed [40] for identification purposes. Recently, the use of RFID tags also for an intraoral continuous monitoring applications, such as saliva analysis to detect the risk of hearth attack, has been proposed [41] even if not implemented yet.…”
Section: The Wireless Communication Sub-systemmentioning
confidence: 99%
“…The application of this passive approach for intraoral sensing has been already proposed and successfully implemented [38,39], in cases where the sensors is located just in the mouth and outside the tooth. However, the use of RFID passive tags to be put inside the tooth has been proposed and experimentals on animals have been performed [40] for identification purposes. Recently, the use of RFID tags also for an intraoral continuous monitoring applications, such as saliva analysis to detect the risk of hearth attack, has been proposed [41] even if not implemented yet.…”
Section: The Wireless Communication Sub-systemmentioning
confidence: 99%
“…Radio Frequency Identification (RFID) is a rapidly growing technology finding applications in a multitude of fields including in healthcare settings [30], [31], [32], [33], [34]. It has been suggested that RFID technology holds the promise to contribute very significant improvements to the future of the healthcare industry [35], [36].…”
Section: Our Innovation Effortsmentioning
confidence: 99%
“…Tags typically deployed in animals or humans are usually rod-shaped, with passive and read-only characteristics [8,9]. However, sheet-form tags may be suitable for insertion into dental prostheses [10].…”
Section: Rfid Tagsmentioning
confidence: 99%